ADVANCEMENT OF CONSULTING SERVICES BASED ON THE USE OF INTEGRATED MARKETING COMMUNICATIONS - V. Zhukov; M. Zhukova (Вестник университета, 2018)
In its activity consulting companies when choosing a service promotion tool are guided by the principles and features of specific characteristics of both services in general and consulting services. It requires consulting companies to develop a single systemic multichannel communication aimed at establishing two-way long-term contact with the target market integrated marketing communications.The main tools of integrated marketing communications: advertising, public relations, sales promotion and direct marketing - has been analyzed in detail. The problems are shown, the solution of which is directed to use each instrument of integrated marketing communications, as well as the possibilities of their use depending on the type of the market, the type of goods and services, the characteristics of consumer behavior, the market situation